The Effectiveness of The Leaflet Media as A Health Promotion Effort to Improve Pregnant Women's Knowledge About Prevention of Mother to Child Transmission of HIV - Ina Kuswanti; Lusa Rochmawati (Alma Ata University Press, 2020)
HIV-AIDS cases in Indonesia have increased every year in women aged 15-49 years. This is because many men have had unsafe sex, which spreads it to their sexual partners. Prevention of mother-to-child transmission of HIV is an effective intervention. One form of its activities is increasing correct and comprehensive knowledge about the prevention of HIV/AIDS transmission, eliminating stigma and discrimination through health promotion (Permenkes RI, 2013). Forms of health promotion that have been carried out through counseling and distributing leaflets. To determine the effectiveness of leaflet media as an effort to promote health in increasing the knowledge of pregnant women about preventing mother-to-child transmission of HIV (PMTCT). This is a quasi experimental quantitative research with a pretest-postest design. The research sample was 25 respondents of pregnant women who live in DIY. The sampling technique used was purposive random sampling. The instrument was a questionnaire on the prevention of mother-to-child HIV transmission. Analysis of data using non-parametric Wiloxon test. Characteristics of pregnant women respondents in terms of age, less than 20 years (1); 21-35 years (22); and over 35 years of age (2). Education of pregnant women respondents: basic education (1); secondary education (9); and higher education (9). The mean value of pre-test knowledge of pregnant women was 86.88. While the average post test score is 94.24. The results showed that there was a difference of 14.64 in the pre-test and post-test scores, meaning that there was an increase in the knowledge of pregnant women before being given leaflet media and after being given leaflet media about preventing mother-to-child transmission of HIV. The results of the effectiveness test used the non-parametric Wiloxon test, the significant value of the normality test was <0.05, meaning that the data were not normally distributed. There are differences in knowledge before being given and after leaflet media were given about prevention of mother-to-child transmission of HIV. Leaflet media is effective as a health promotion effort to increase the knowledge of pregnant women about preventing HIV transmission from mother to child